The Potential of Modelling Co-Teaching in Pre-Service Education - Drescher, Talya (Journal of University Teaching and Learning Practice, 2017)
Two studies aimed to document the process of preparing for and teaching collaborative education courses and to determine students’ perception of collaboration and inclusion as a result of taking the course. Two sessions of collaborative teaching run by different professor dyads were studied over two 10-week quarters at a large public university. Multiple sources of data were collected. Ultimately, modelling collaboration and a positive attitude toward disability, collaboration, and inclusion provided professors an opportunity to help guide and shape pre-service teachers’ attitudes.